LEARNING STYLES OF BIOLOGY STUDENTS AT UNIVERSITAS NEGERI PADANG - Rahmadhani Fitri; Mudjiran Mudjiran (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Learning style is a way to act and use stimuli in learning. When the lecturer wants to teach a learning material, the lecturer teaches according to the tendencies of student learning styles, because in general students have different learning styles. The learning style carried out by a student varies from one to another depending on the habits that are often carried out. There are three learning styles of a person, namely visual, auditory, and kinesthetic learning styles. Knowing the learning styles that students have can create a pleasant learning atmosphere for students, generate motivation to learn, and reduce conflicts that arise as a result of learning. This study aims to identify the learning styles of first-year students at the Biology Department, FMIPA, Universitas Negeri Padang. This research is a descriptive study using an instrument in the form of a learning style questionnaire. Data were analyzed with descriptive statistics. The results of the study found that the first year students of the Biology Department, FMIPA, Universitas Negeri Padang had a dominant visual learning style then auditory, and finally kinesthetic. This can happen because basically these students like learning in which the material is presented using lots of pictures, videos, schemes, or diagrams. With the dominance of visual learning styles in the first year students of the Biology Department, it is hoped that lecturers can wisely choose appropriate learning to facilitate student learning styles by choosing strategies, methods, models, approaches, and learning media that are suitable and suitable regardless of the learning style used. owned by other students who are dominantly auditory and kinesthetic.